High output triboelectric nanogenerator based on PTFE and cotton for energy harvester and human motion sensor - Zhang, Zhongxing; Cai, Jun (Current applied physics, 2021)
Recently, a novel mechanical energy harvesting method named triboelectric nanogenerator (TENG) is reported, and it has aroused great repercussions in the academic fields. But, the complex preparation process still limits its wide application. In this paper, the cotton film was used as the triboelectric material to fabricate a novel wearable TENG (W-TENG). The polytetrafluoroethylene (PTFE) film and cotton film play the role of triboelectric pair. The W-TENG can be used to harvest low-frequency mechanical energy in our environment, especially for human body mechanical energy, and then convert them to electrical energy. In addition, the cotton coated with conductive ink plays the role of conductive material for TENG. The Voc and Isc of W-TENG can reach 556 V and 26 μA, respectively. As for the maximum power density of W-TENG, it can arrive at 0.66 mW/cm2. Also, a combined W-TENG was proposed to improve the electrical output. Moreover, the W-TENG can play the role of human motion sensor for human walking posture monitoring. This will open up a new path for the preparation of high output TENG at low cost, and promote the TENG devices in the field of sports monitoring. [Display omitted] •We firstly reported a wearable TENG (W-TENG) based on the polytetrafluoroethylene (PTFE) film and cotton film to harvest mechanical energy in our environment.•The results also show that the W-TENG has wonderful charging effect and excellent reliability.•The W-TENG can play the role of human motion sensor for human walking posture monitoring.